Study on the Identification Method of Gear Spalling Fault - Shengli Wu; Yimin Shao; Wenting Xing; Xiaochun Jian (Jixie chuandong)
Spalling and pitting are prone to be produced on the tooth surfaces in the meshing process, which seriously affects the stability and reliability of gear meshing. The time-varying meshing stiffness model and six-degree-of-freedom model of gear meshing are established, the Matlab wavelet toolbox is used to generate an adaptive wavelet which is similar to the original signal. The time frequency characteristic change rule of vibration signal is illustrated. Agreement between the results of the dynamic model and the experimental results validates the effectiveness of the generated adaptive wavelet method which is used to analyze the spalling defect. The results provide theoretical basis and practical support for the gear defect size identification in black-box condition.